2014
DOI: 10.1111/jsm.12633
|View full text |Cite
|
Sign up to set email alerts
|

Gender Identity Rather Than Sexual Orientation Impacts on Facial Preferences

Abstract: Introduction Differences in facial preferences between heterosexual men and women are well documented. It is still a matter of debate, however, how variations in sexual identity/sexual orientation may modify the facial preferences. Aim This study aims to investigate the facial preferences of male-to-female (MtF) individuals with gender dysphoria (GD) and the influence of short-term/long-term relationships on facial preference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 43 publications
(54 reference statements)
1
12
0
Order By: Relevance
“…In addition, a recent study found that FtM GD individuals show stronger more female-typical otoacustic emissions compared to control boys, suggesting that boys with GD might have been exposed to relatively lower amounts of androgens during early development [45]. In line with these studies, it has also been reported that MtF individuals have female-typical facial preferences in terms of sexual attraction [46]. It has also been postulated that there may be genetically based systemic sex hormone abnormalities that do no cause abnormalities of the reproductive anatomy, but nevertheless influence brain and behavior [33].…”
Section: Introductionsupporting
confidence: 70%
“…In addition, a recent study found that FtM GD individuals show stronger more female-typical otoacustic emissions compared to control boys, suggesting that boys with GD might have been exposed to relatively lower amounts of androgens during early development [45]. In line with these studies, it has also been reported that MtF individuals have female-typical facial preferences in terms of sexual attraction [46]. It has also been postulated that there may be genetically based systemic sex hormone abnormalities that do no cause abnormalities of the reproductive anatomy, but nevertheless influence brain and behavior [33].…”
Section: Introductionsupporting
confidence: 70%
“…Indeed, the impact of prenatal hormones on gender identity development is still not clear [56]. The effect of prenatal androgen exposition has been explored with studies conducted on typical population by using indirect measures, such as finger ratio (i.e., the length of the index finger to the ring finger length [57]), which is higher in females since intrauterine life [58][59][60][61][62][63][64].…”
Section: The Shaping Effect Of Sex Hormones and Involved Genes On Bramentioning
confidence: 99%
“…3e5 However, masculinity and femininity were also defined as specific psychological traits, described as 2 opposed sets of stereotypical characteristics derived from sociocultural constructs. 4,6,7 In the seventies, this vision was modified by the introduction of the "androgyny" concept, indicating the harmonious combination of high levels of masculinity and femininity in the same person, beyond the gender identity and the biological sex's expressions. 8,9 Although definitions, origins, and relationships of sex roles have been considered on the basis of sociocultural aspects, 10 personality characteristics may also play a role modulating the expression of masculinity and femininity.…”
Section: Introductionmentioning
confidence: 99%